Influence of footwear, foot-strike pattern and step frequency on spatiotemporal parameters and lower-body stiffness in running. Issue 3 (1st February 2022) - Jaén-Carrillo, Diego; García-Pinillos, Felipe; Latella, Christopher; Moore, Stephanie R.; Cartón-Llorente, Antonio; Roche-Seruendo, Luis E.
ABSTRACT: This study aimed to determine the influence of footwear condition, foot-strike pattern and step frequency on running spatiotemporal parameters and lower-body stiffness during treadmill running. Thirty-one amateur endurance runners performed a two-session protocol (shod and barefoot). Each session consisted of two trials at 12 km · h −1 over 5 minutes altering step frequency every minute (150, 160, 170, 180 and 190 spm). First, participants were instructed to land with the heel first; after completion, the same protocol was repeated landing with the forefoot first. Repeated measures ANOVAs showed significant differences for footwear condition, foot-strike pattern and step frequency for each variable: percent contact time, percent flight time, vertical stiffness and leg stiffness (all p < 0.001). The results demonstrate greater estimated vertical and leg stiffness when running barefoot for both foot-strike patterns showing the largest values for barefoot+forefoot condition. Likewise, both vertical and leg stiffness became greater as step frequency increased. The proper manipulation of these variables facilitates our understanding of running performance and assist in training programmes design and injury management.